Peningkatkan Hasil Belajar melalui Pendekatan Culturally Responsive Teaching (CRT) pada Materi Bangun Datar Kelas 2 SDN Uteran 01 - Kiki Echa Ardianti; Vivi Rulviana; Aning Triastuti (PT PUSTAKA CENDEKIA GROUP, 2025)
The main challenge in mathematics learning at the elementary school level, particularly in the topic of flat shapes, is often related to students' low interest in mathematics, which is perceived as abstract and difficult to understand. The purpose of this study is to analyze the improvement of learning outcomes through a Culturally Responsive Teaching (CRT) approach in the topic of flat shapes in grade 2 at SDN Uteran 01. The research method used is Classroom Action Research (CAR) in two cycles, with a total of 8 students participating in the study. Data collection techniques include tests, and the data analysis technique used is descriptive analysis. The results of the study indicate that the Culturally Responsive Teaching approach, using examples of traditional foods such as wajik , onde-onde jenang, lapis, klepon in the mathematics lesson on flat shapes, has proven effective in improving students' learning outcomes. This is evidenced by the improvement in learning outcomes, where in cycle 1, most students achieved very poor results, but in cycle 2, the majority of students achieved good results.